Gambaran Faktor Risiko Penyakit Demam Berdarah Dengue pada Anak di Wilayah Kerja Puskesmas Tabanan I - Desak Agung Indah Praharsini Dewi; Anak Agung Oka Lely; Sri Agung Aryastuti (Aesculapius Medical Journal, 2023)
Dengue hemorrhagic fever (DHF) is one of the most concerning infectious disease problems. Tabanan regency has one of the highest case fatality rate (CFR) of dengue hemorrhagic fever with the Tabanan sub-district having a relatively high increase on 2018 â€“ 2019 period. DHF tends to affect children and increasing its mortality rate. There are several risk factors contributing to the higher incidence of DHF such as human as its host-related risk factors, mosquito as its vector-related risk factors, and the environment itself as one of the risk factors. This study used descriptive methods with cross sectional study design. The data collected in this study is primary data gathered by questionnaire on October â€“ Desember 2021. The subject were children under the age of 18 years in the Puskesmas Tabanan I with criteria qualified, as many as 90 peoples. Univariative sampling by frequency distribution table as its data analysis method. The result of this study indicates that the majority of the dengue hemorrhagic fever cases occurs in the age group of 10-14 years old (35,42 %) and occur mostly in men (58,33 %). Regarding host-related risk factors, children with more outdoor activity (68,75 %) and infrequent us of mosquito repellent (77,09 %) were associated with higher incidence of DHF and regarding the â€œPSNâ€ activity, higher incidence was found in children/family with habitual garbage cleaning of only once in two weeks (95,82 %), keeping their garbage uncovered (66,67 %), and never recycled their garbage (50 %). Most of the children with DHF rarely used abate in their bathroom(68,75%) and not having the habit of hanging their clothes in the room (64,58 %). From the results of this study, it is hoped that it can give special attention to groups at risk and be used as a reference for further research.